SRA inhibition improves antitumor potency of antigen-targeted chaperone vaccine - Qian, Jie; Yu, Xiaofei; Liu, Zheng; Cai, Jinyang; Manjili, Masoud H.; Yang, Hu; Guo, Chunqing; Wang, Xiang-Yang (Frontiers in Immunology, 2023)
We have previously demonstrated that scavenger receptor A (SRA) acts as an immunosuppressive regulator of dendritic cell (DC) function in activating antitumor T cells. Here we investigate the potential of inhibiting SRA activity to enhance DC-targeted chaperone vaccines including one that was recently evaluated in melanoma patients. We show that short hairpin RNA-mediated SRA silencing significantly enhances the immunogenicity of DCs that have captured chaperone vaccines designed to target melanoma (i.e., hsp110-gp100) and breast cancer (i.e., hsp110-HER/Neu-ICD). SRA downregulation results in heightened activation of antigen-specific T cells and increased CD8+ T cell-dependent tumor inhibition. Additionally, small interfering RNA (siRNA) complexed with the biodegradable, biocompatible chitosan as a carrier can efficiently reduce SRA expression on CD11c+ DCs in vitro and in vivo. Our proof-of-concept study shows that direct administration of the chitosan-siRNA complex to mice promotes chaperone vaccine-elicited cytotoxic T lymphocyte (CTL) response, culminating in improved eradication of experimental melanoma metastases. Targeting SRA with this chitosan-siRNA regimen combined with the chaperone vaccine also leads to reprogramming of the tumor environment, indicated by elevation of the cytokine genes (i.e., ifng, il12) known to skew Th1-like cellular immunity and increased tumor infiltration by IFN-+CD8+ CTLs as well as IL-12+CD11c+ DCs. Given the promising antitumor activity and safety profile of chaperone vaccine in cancer patients, further optimization of the chitosan-siRNA formulation to potentially broaden the immunotherapeutic benefits of chaperone vaccine is warranted.